Mondo dell'Illuminismo. - Ferrone, Vincenzo, author. Link
1 online resource (vi, 226 pages)
Keywords: "The Enlightenment was a laboratory of modernity that changed the history of the Western world, helping to bring about globalisation and the rise of a powerful intellectual class. It gave the scientific revolution new methods and a new purpose by ushering in the sciences of man. At the same time, it constantly interrogated these new sciences, wary of the possibility that they might lead to discrimination rather than emancipation. The late Enlightenment, the most mature and productive period, developed its values and political ideals, such as the concept of liberty and of a constitutional and "republican" government, through its confrontation with the ancien régime, the slave trade and imperial colonialism, and the betrayal of the revolutionary ideals in the Americas. The World of the Enlightenment is a wide-ranging discussion of one of the most important cultural phenomena of the modern era. It covers topics from the scientific (such as the approaches of empiricism and humanism), the political (the rights of man, slavery, and colonial independence), and the artistic (modern art and public opinion). The author discusses these topics thematically in ten chapters. This book will appeal to scholars and students alike studying the Enlightenment and the history of intellectualism, as well as all those interested in the history of modern science, politics, and culture"--